Uterine sarcoma – time is worth its weight in gold - Dominik Pruski; Sonja Millert-Kalińska; Radosław Mądry; Klaudia Kotynia; Tadeusz Pawełek; Damian Rusek; Andrzej Zmaczyński; Robert Jach; Marcin Przybylski (Polish Journal of Pathology, 2023)
Leiomyosarcoma is one of the most common types of soft tissue sarcoma in adults, and it can occur in almost any part of the body. Uterine leiomyosarcoma constitutes 1% of all gynaecological tumours. Most diagnosed sarcomas are not even suspected before surgery. However, in recent years, awareness of their presence in society has increased. Our case aims to draw attention to the need for better cooperation between pathologists and clinicians and reduce the time from suspicion of the disease to final diagnosis.